Surgical fixation with K-wires versus plaster casting in the treatment of dorsally displaced distal radius fractures: protocol for Distal Radius Acute Fracture Fixation Trial 2 (DRAFFT 2) - Achten, J; Sones, W; Dias, J; Hedley, H; Cook, J; Dritsaki, M; Ee Png, M; Gray, A; Lamb, S; Costa, M (BMJ Publishing Group, 2019)
Introduction: Optimal management of distal radius fractures in adults remains controversial. Previous evidence and current clinical guidelines tell us that, if a closed reduction of a dorsally displaced fracture is possible, Kirschner wires (K-wires) are the preferred form of surgical fixation. However, the question remains whether there is any need to perform surgical fixation following a successful closed reduction, or is a simple plaster cast as effective? This is the protocol for a randomised controlled trial of manipulation and surgical fixation with K-wires versus manipulation and casting in the treatment of dorsally displaced distal radius fractures. Methods and analysis: Adult patients with an acute dorsally displaced fracture of the distal radius are potentially eligible to take part. Prior to surgery, baseline demographic data, radiographs, data on pain/function using the Patient-Rated Wrist Evaluation Score (PRWE) and health-related quality of life (HRQoL) using the EuroQoL 5-dimension 5-level (EQ-5D-5L) will be collected. A randomisation sequence, stratified by centre, intra-articular extension of the fracture and age, will be administered via a secure web-based service. Each patient will be randomly allocated to either ‘manipulation and surgical fixation with K-wires’ or ‘manipulation and plaster casting’. A clinical assessment, radiographs and records of early complications will be recorded at 6 weeks. PRWE and HRQoL outcome data will be collected at 3, 6 and 12 months post-randomisation. Further information will be requested with regard to healthcare resource use and any complications. Ethics and Dissemination: The National Research Ethic Committee approved this study on 6 October 2016 (16/SC/0462). The National Institute for Health Research Health Technology Assessment monograph and a manuscript to a peer-reviewed journal will be submitted on completion of the trial. The results of this trial will substantially inform clinical practice on the clinical and cost-effectiveness of the treatment of this injury.